„Gościńce trwałe i wieczne” zamiast „olbrzymich głazów samotnych”: neorealizm w myśli politycznej Prawa i Sprawiedliwości - Paruch, Waldemar (W kręgu wyobrażeń zbiorowych. Polityka, władza, społeczeństwo, 2019)
The article is the analysis of Law and Justice party, perceived as neorealistic (as opposed to neoliberalism). The argument between neorealists– neoliberals implied polarisation, concentration, political mobilisation in Poland. The adversary of Law and Justice is Civic Platform – a neoliberal party. In theoretical background the subject of the competition is realism. The choice of the means to achieve goals is based on historic, cultural and geopolitical analysis. For Civic Platform realism is based on the adjustment of means for the political disposal. In the article four dimensions were analysed: cognitive, conceptual, axiological and programmatic. One of the most important consequence of realism for Law and Justice party is hard politics visible in international affairs.